The Implementation of Contextual Learning Approach in E-learning based on Weblog toward Students Learning Achievements - Siti Osa Kosassy; Nurhizrah Gistituati; Jalius Jama; Maria Montessori (Journal of Counseling and Educational Technology, 2018)
Technology leads the essence of education into interactive and creative process. The objective of this study is to find out the effect of CTL approach in e-learning based on weblog toward the students learning achievement. The design of the study is experimental research design. The population of this research was public administration students at STIA Padang academic year 2018/2019 which consisted of two classes. The sample of this research was all of public administrations students. The sample was class A as an experimental class and class B as a  control class. Test, interview and observation were used as a research instruments. The results of this study reveal that: (1) the increasing of organization and management learning achievement in Experimental Class is 70% while in Control Class 55.7% with differences 14.3%. it means, there is a progress of student learning achievement activity taught by CTL approach in e-learning based on weblog, (2) the students also have positive response and high motivation than before in following the teaching and learning process. Hence, CTL approach based on weblog give a positive effect to the students learning outcomes and it is one of effective e-learning media in teaching.